Penggunaan Media Pembelajaran Mahasiswa Jurusan Teknik Sipil Selama Program Pengalaman Lapangan (PPL) - Anisa Humaeroh (Jurnal Pensil : Pendidikan Teknik Sipil, 2014)
This study aims to determine the use of learning media by civil engineering students during field experience program. This research was conducted at the Department of Civil Engineering, State University of Jakarta. The time period of research is January-June 2011. The research population is Civil EngineeringStudents UNJ Even Semester, 2010/2011 Academic Year. The sample used are 20 PPL students from 35 Department of Civil Engineering PPL students who did field experience program and 60 vocational school students. This research used survey method with descriptive approach. Questionnaire instruments are used in collecting the data. The instruments were tested first before used in research. Test results showed that 21 questions are valid and reliable (rtabel = 0.532). The analysis of data is using qualitative descriptive techniques with percentage.The results showed that PPL students using instructional media in accordance with the learning purposes that are analyzing the concepts and relationships,memorizing, requires higher-level thinking, and implementing physical procedures. In addition, PPL students have usedall learning media such asprinting media, programs (power point), boards, real thing, video with media devices LCD projector and computer / laptop. In this case the largest percentage is to use the board media and the smallest percentage isto use video media.The conclusion of this study is that all PPL students of Civil Engineering were usinglearning media appropriate to the learning objectives